FINANCIAL DISTRESS, SIZE, AGE, DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: BUKTI EMPIRIS DARI INDONESIA SELAMA MASA PANDEMI COVID-19 - Putra, Kiki Satria Hutama; Wahyuni, Ersa Tri; Fitrijanti, Tettet (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This study aims to investigate the influence of financial distress, company size, and company age on corporate social responsibility disclosure before and during the COVID-19 pandemic. We consider that the existence of this unprecedented situation is useful for understanding how the dynamics of corporate social responsibility disclosure changes during the COVID-19 pandemic. Using purposive sampling method, 114 companies in energy, raw materials, industry, and infrastructure sector that listed in Indonesian Stock Exchanges were selected as research samples. Data were analysed using multiple linear regression analysis. The results revealed that financial distress and company size have positive effects on corporate social responsibility disclosure in the period before and during the COVID-19 pandemic. Meanwhile, the age of the company in the period before and during the COVID-19 pandemic has no effect on corporate social responsibility disclosure.